Swimming speed in relation to training load - Wojta, Eric (My University, 2009)
The amount and intensity of training a subject enters into will impact athletic performance. Previous studies have demonstrated that fitness and fatigue achieved during training will impact performance. This study compared the subject's performance in time trials to the subject's level of fitness minus the level of fatigue (Fit-Fat) as calculated for each subject. Twelve male and twenty-four female swimmers (n = 36) volunteered to participate in eleven weeks of varied intensity and duration training sessions while performing 100 yard time trials at the end of each training phase. Subjects' percent improvements on the time trial (NormTT) were compared to the Fit-Fat of each swimmer during each training phase. At the end of the seven week general endurance phase (GETT) a 0.205 correlation was observed between the two variables with p = 0.229. The increased loading phase (ILTT) yielded a 0.159 correlation with p = 0.355 while the decreased loading phase (DLTT) yielded a 0.201 correlation with 0 = 0.254. Subjects averaged during the GETT a Fit-Fat of -47.417and a 2.563 percent faster NormTT. Average values during the ILTT were Fit-Fat of -80.028 and a 1.825 percent faster Normr1T' and during the DLTT a Fit-Fat of 220.861 with a 4.260 percent faster NormTT. Mean NonnTT for the DLTT proved to be significantly faster than the mean NormTT for the GETT and ILTT (p < 0.05). The use of Fit-Fat in an attempt to predict a subject's percent improvement on performance proved not to be successful at a significant level (p < 0.05).
Keywords: Swimming -- Physiological aspects; Swimming -- Training